The little boy and Blue Bird - Petek Levokov, Milan (knjige, 2023)
This is a collection of six children’s stories, tales and fables set in today’s busy world—a world of cars, computers, TVs, modern technology and school. However, another world exists parallel to this one—a surreal world of talking animals and things, dragons, elves, flying carpets ... In this world, children always play the main role—they are the only ones who can understand the world as a whole, as they carry none of the burdens that come with being an adult. All of the tales are told with wit and humour.